Information and communication technologies in support of the tourism industry - Pease, Wayne, 1953-; Rowe, Michelle, 1961-; Cooper, Malcolm, 1946- (Hershey, PA : Idea Group Pub., 2007)
"This book examines the process of transformation as it relates to the tourism industry, and the changes to that industry from modern electronic communications. It covers not only geographically supportive technologies in communication, but also in terms of culture, economics, marketing, social, and regional issues"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Tourism -- Information technology